SEM study of debonding /pull-out features & FTIR analysis of bonding in fly ash- epoxy particulate composites - Ibraheem1, Shahad; Standard, Owen; Pramod, Koshy; Devasahayam, Sheila; Bandyopadhyay, Sri (2016)
This research utilises as received coal power fly ash (FA) as a value-added component added to epoxy resin for making a superior matrix for fibre reinforced composites in load-bearing applications. The epoxy resin used in this project was DGEBA cured by cycloaliphatic polyamine at 120 Co for 2 hours. A fly ash with particle size ranging between 2 – 20 micron was added to the epoxy in 0, 10, 20, 30, 40 & 50 wt% proportions. Scanning Electron Microscopy (SEM) of tensile fracture surfaces of the composites using ASTM D638 tensile samples provide significant evidence of Fly Ash debonding and pull-out from the epoxy matrix indicating good mechanical bonding between FA and epoxy matrix. Fourier transform infrared spectroscopy (FTIR) of pure epoxy, pure fly ash and selective composites (20 and40 wt % FA-epoxy composites) shows distinct evidence of fly ash functional groups’ interaction with the epoxy matrix. Some selected SIMS (secondary ion mass spectrometry) results are presented for the 20wt % fly ash /epoxy composites.